Stoicism and performance : a joyful materialism - Power, Cormac (Consciousness, literature & the arts ;, 2020)
Power's Stoicism and Performance presents Stoicism as a means of navigating key debates and concepts in contemporary theatre and performance. Stoicism has influenced many of the most cited radical thinkers in the discipline of theatre and performance studies; for instance Deleuze, Foucault, Kristeva, Agamben. A central aim of this work is to bring Stoicism more explicitly into the fold of the discipline, and to use Stoicism to think differently about performance. With a series of chapters covering themes such as performativity, embodiment, emotion, affect and spectatorship, this book finds points of encounter between Stoicism and contemporary understandings and practices of performance. It presents these encounters as modes of transformative experience in relation to our being in the world.